Analisis Kesiapan Teknologi Informasi dan Implementasi Aplikasi Antropometri Nutrisi Anak untuk Optimalisasi Program Makan Bergizi Gratis - Ana Samiatul Milah; Rani Rahmayani; Yanyan Sofiyan (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
The Free Nutritious Meal (MBG) program requires a high-precision monitoring system to ensure its effectiveness in improving children's nutritional status. This study aims to analyze information technology readiness through the development and implementation of the Children's Nutritional Anthropometry (ANA) application. The methodology employs an action research approach involving IT training for 100 health volunteers, digital nutritional counseling, and physical examinations of 500 children. The primary focus of this article is to evaluate how digital infrastructure readiness and technology literacy at the village level influence the accuracy of nutritional monitoring data. The results indicate that the integration of the ANA application significantly accelerates nutritional status reporting and facilitates the distribution of targeted nutritional interventions. Furthermore, the enhancement of IT readiness among health volunteers reduces human error in data entry, ensuring that the MBG program is supported by a robust and reliable decision support system.